Lithium ion sieve, chemically strengthened microcrystalline glass and electronic equipment
By providing a lithium-ion sieve with reasonable composition, the existing lithium-ion sieve has been solved, and the problem of low decomposition and lithium absorption efficiency at high temperatures is achieved, high thermal stability and high lithium absorption efficiency are achieved, and the damage resistance and product yield of microcrystalline glass is significantly improved.
Patent Information
- Application Number
- CN202311232131.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-03-21
AI Technical Summary
Existing lithium-ion sieves are easy to decompose at high temperatures, affecting the pH of molten salts, and have low lithium absorption efficiency, resulting in a decrease in damage resistance of microcrystalline glass, which is called lithium poisoning.
A lithium ion sieve is provided, and its composition includes 40%≤SiO2≤55%, 15%≤Al2O3≤30%, 20%≤Na2O<30%, 0%≤MgO≤10%. The lithium ion sieve has high thermal stability and high lithium absorption efficiency, and can maintain structural stability at high temperatures, reduce decomposition, and support the chemical strengthening process of microcrystalline glass.
When used in conjunction with molten salt, the lithium ion sieve is not easy to soften or decompose, maintaining the pH of molten salt, improving the damage resistance of microcrystalline glass, reducing surface pollution, and significantly improving the yield and performance of the product.
Smart Images

Figure CN119661092A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of glass technology, and in particular, to lithium ion screens, chemically strengthened microcrystalline glass, and electronic equipment. Background Art
[0002] Glass-ceramics is a composite material composed of glass phase and microcrystalline phase. It can be used as a cover material (CoverGlass) to give mobile electronic devices such as mobile phones excellent drop resistance and anti-fall performance. The damage resistance of glass-ceramics comes from its excellent intrinsic properties such as high Young's modulus and fracture toughness, and also from the residual compressive stress generated by the chemical strengthening process.
[0003] The core of the chemical strengthening process is to use large-radius alkali metal ions such as Na + , K + Replacement of small radius alkali metal ions Li in glass + , resulting in local "crowding" to form a surface compressive stress layer. With the increase of strengthening degree, Li + The concentration will gradually increase. According to the surface chemical equilibrium, Li + The increase in concentration will inevitably inhibit the exchange reaction of large-radius ions in the molten salt replacing small-radius ions in the microcrystalline glass, affecting the performance of the microcrystalline glass. Compared with ordinary glass, the surface chemical equilibrium of microcrystalline glass-high-temperature molten salt is more sensitive to Li + Very sensitive to concentration changes, even at the ppm level + Changes in concentration will also cause a significant decrease in compressive stress intensity, thereby reducing the damage resistance of the microcrystalline glass. The size expansion of the microcrystalline glass will also decrease rapidly, resulting in a decrease in yield.
[0004] This molten salt contains Li + The problem that the increase in concentration will reduce the stress strength and product yield of microcrystalline glass is called lithium poisoning. + The adverse effects of poisoning on product performance and yield can be replaced by new molten salt, but this will increase costs and reduce efficiency. Alternatively, an ion sieve that can specifically purify lithium ions at the ppm level in the molten salt can be used, but the existing lithium ion sieve has low lithium absorption efficiency and poor thermal stability. It is easy to decompose at high temperatures, which affects the pH value of the molten salt and even corrodes the surface of the microcrystalline glass, causing the surface of the microcrystalline glass to become atomized. Summary of the invention
[0005] The present application proposes a lithium ion sieve, chemically strengthened microcrystalline glass, and electronic equipment. The lithium ion sieve provided by the present application has both high thermal stability and high lithium absorption efficiency. When used in conjunction with molten salt, it is not easy to soften or decompose, which is beneficial to maintaining the pH value of the molten salt and can support the chemical strengthening process of microcrystalline glass at higher temperatures.
[0006] In a first aspect, the present application provides a lithium ion sieve, which is used for chemically strengthening microcrystalline glass. In terms of molar percentage, the lithium ion sieve includes the following components: 40%≤SiO2≤55%, 15%≤Al2O3≤30%, 20%≤Na2O<30%, and 0%≤MgO≤10%.
[0007] In some embodiments, in terms of molar percentage, 40%≤SiO2≤55%. The molar ratio of SiO2 can be 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54% or 55%, etc., and can also be other values within the range of 40% to 55%, which is not limited here.
[0008] The molar ratio of Al2O3 can be 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29% or 30%, etc., and of course it can also be other values within the range of 15% to 30%, which is not limited here.
[0009] The molar ratio of Na2O can be specifically 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 28.5%, 29% or 29.5%, etc., and of course it can also be other values within the range of 20% to 30%, which is not limited here.
[0010] The molar content of MgO may be 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 8.5%, 9% or 10%, etc., and may also be other values within the range of 0% to 10%, which is not limited here.
[0011] Na2O is an exogenous substance and an important carrier for purifying lithium ions in molten salt through Na+-Li+ ion exchange reaction. However, too high a content of Na2O can easily introduce too much non-bridging oxygen, resulting in a decrease in the glass transition temperature of the lithium ion sieve. Al2O3 and MgO can form Al-containing in the SiO2 microstructure. 3+ / Mg 2+ Four-coordinate, containing Al 3+ / Mg 2+ The tetraligand is an effective channel for lithium ion transport and can effectively improve the lithium absorption efficiency of the lithium ion sieve. Preferably, in terms of molar percentage, 20%≤Na2O≤29%, 0%≤MgO≤4.5%.
[0012] In some embodiments, in terms of molar percentage, 60%≤SiO2+Al2O3≤80%. By controlling the total amount of SiO2+Al2O3, SiO2 and Al2O3 can form polar covalent bonds and ionic bonds, which is beneficial to maintaining the structural stability of the lithium ion sieve under high temperature conditions and reducing the decomposition of the lithium ion sieve.
[0013] In some embodiments, in terms of molar percentage, 0.8≤Na2O / (MgO+Al2O3)≤1. Controlling 0.8≤Na2O / (MgO+Al2O3)≤1 within this range can better achieve a balance between the high glass transition temperature and lithium absorption efficiency of the lithium ion sieve, so that the lithium ion sieve can have both high thermal stability and high lithium absorption efficiency when used in conjunction with molten salt, and is not prone to softening or decomposition.
[0014] In some embodiments, the glass transition temperature Tg of the lithium ion sieve satisfies: 600≤Tg≤800° C. The lithium ion sieve can support the chemical strengthening process of microcrystalline glass at a higher temperature, has low corrosiveness to microcrystalline glass, and greatly reduces pollution to the surface of microcrystalline glass.
[0015] In a second aspect, the present application provides a lithium ion sieve, which is used for chemically strengthening microcrystalline glass. In terms of molar percentage, the lithium ion sieve comprises the following components: 35%≤SiO2≤45%, 10%≤Al2O3≤20%, 30%≤Na2O≤45%;
[0016] The lithium ion sieve also includes La2O3 and / or ZrO2, in molar percentage, 0%≤La2O3≤15%, 0%≤ZrO2≤10%.
[0017] Specifically, the molar ratio of SiO2 can be 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44% or 45%, etc., and of course it can also be other values within the range of 35% to 45%, which is not limited here.
[0018] The molar ratio of Al2O3 can be specifically 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%, etc., and of course it can also be other values within the range of 10% to 20%, which is not limited here.
[0019] The molar ratio of Na2O can specifically be 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44% or 45%, etc., and of course it can also be other values within the range of 30% to 45%, which is not limited here.
[0020] The molar ratio of La2O3 can be 0%, 0.5%, 1%, 3%, 5%, 7%, 9%, 10%, 12%, 13%, 14% or 15%, etc., and of course it can also be other values within the range of 0% to 15%, which is not limited here.
[0021] The molar ratio of ZrO2 can be specifically 0%, 0.5%, 1%, 3%, 5%, 7%, 9% or 10%, etc., and of course it can also be other values within the range of 0% to 15%, which is not limited here.
[0022] In some embodiments, 0%<La2O3+ZrO2≤25%. It can be understood that ZrO2 and La2O3 can effectively reduce the proportion of non-bridging oxygen in the microstructure of the glass and improve the thermal stability of the lithium ion sieve.
[0023] In some embodiments, by mole percentage, 30%≤Na2O≤38%, 5%≤La2O3+ZrO2≤25%.
[0024] In some embodiments, in terms of molar percentage, 40%≤SiO2+Al2O3≤60%. By controlling the total amount of SiO2+Al2O3, SiO2 and Al2O3 can form polar covalent bonds and ionic bonds, which is beneficial to maintaining the structural stability of the lithium ion sieve under high temperature conditions and reducing the decomposition of the lithium ion sieve.
[0025] In some embodiments, in terms of molar percentage, 1≤Na2O / (La2O3+ZrO2)≤15. Controlling 1≤Na2O / (La2O3+ZrO2)≤15 within this range can better achieve a balance between the high glass transition temperature and lithium absorption efficiency of the lithium ion sieve, so that the lithium ion sieve can have both high thermal stability and high lithium absorption efficiency when used in conjunction with molten salt, and is not prone to softening or decomposition.
[0026] In some embodiments, the glass transition temperature Tg of the lithium ion sieve satisfies: 500≤Tg≤700°C.
[0027] In a third aspect, the present application provides a chemically strengthened glass-ceramics, wherein the chemically strengthened glass-ceramics is prepared by the following method:
[0028] The glass-ceramics is placed in a molten salt containing the above-mentioned lithium ion sieve to carry out chemical ion exchange to obtain chemically strengthened glass-ceramics.
[0029] In some embodiments, the molten salt includes at least one of sodium nitrate, sodium chloride, potassium nitrate, and potassium chloride.
[0030] In a fourth aspect, the present application provides a glass structural member, wherein the glass structural member includes the above-mentioned chemically strengthened microcrystalline glass.
[0031] In a fifth aspect, the present application provides a display screen, comprising a cover plate, wherein the cover plate is made of the above-mentioned chemically strengthened microcrystalline glass.
[0032] In a sixth aspect, the present application provides an electronic device, which includes the above-mentioned glass structural member or the above-mentioned display screen.
[0033] Compared with the prior art, the lithium ion sieve provided in the present application has a reasonable structure and composition. When used in conjunction with molten salt, it can have both high thermal stability and high lithium absorption efficiency, is not prone to softening or decomposition, and is beneficial to maintaining the pH value of the molten salt. The lithium ion sieve can adsorb or extract impure metal ions in the molten salt, which is beneficial to the restoration of the activity of the molten salt, can support the chemical strengthening process of microcrystalline glass at higher temperatures, has little corrosiveness to microcrystalline glass, and greatly reduces pollution to the surface of the microcrystalline glass. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 A comparison chart of the artificial neural network model predicted values and the measured values of the glass transition temperature of the glass sample data provided in the embodiments of the present application;
[0035] Figure 2 A comparison chart of the artificial neural network model predicted value and the measured value of the glass transition temperature of the lithium ion sieve provided in the embodiment of the present application;
[0036] Figure 3 A comparison chart of the lithium absorption efficiency of the lithium ion sieve provided in Example 6 of the present application and the lithium ion sieves provided in Comparative Examples 1 and 2;
[0037] Figure 4 This is a comparison chart of the effects of the lithium ion sieve provided in Example 6 of the present application and the lithium ion sieves provided in Comparative Examples 1 and 2 on the pH value of the molten salt. DETAILED DESCRIPTION
[0038] The technical solution provided by the present invention is further described below in conjunction with specific embodiments and comparative examples, but the present application is not limited to the following embodiments.
[0039] Glass-ceramics is a material composed of a crystalline phase and a glass phase with a uniform and dense structure, among which high-crystallinity, transparent glass-ceramics are the most valuable type of glass-ceramics. Glass-ceramics has a high internal crystallinity, and the grain size can be controlled within a small range. During the crystallization process, the chemical composition of the crystalline phase and the residual glass phase are similar, the refractive index difference is small, the composition changes continuously, and it has high transmittance in the visible light region; at the same time, the large content of the crystalline phase also ensures the mechanical strength of the glass-ceramics. In order to improve the drop resistance and other properties of glass-ceramics, introducing surface compressive stress on the glass surface is a common method for strengthening the glass. Among them, after the glass is chemically strengthened, the alkali metal ions with a smaller radius on the surface are replaced by alkali metal ions with a larger radius. Due to the crowding effect of the alkali metal ions with a larger radius, compressive stress is generated on the glass surface.
[0040] The core of the chemical strengthening process is to use large-radius alkali metal ions such as Na + , K + Replacement of small radius alkali metal ions Li in glass + Alkali metal ions with a larger radius produce a "crowding" effect on the glass surface, thus forming a compressive stress layer of a certain depth on the glass surface. This compressive stress layer can improve the surface hardness of the glass to a certain extent, offset external impact, and prevent the expansion of microcracks, thereby improving the glass's scratch resistance and drop resistance.
[0041] In the process of chemically strengthened glass ion exchange, small ions (Li + ) will be gradually replaced by large ions. As the number of enhanced batches increases, the pure sodium salt Li + The concentration will also increase. The purity of the molten salt has a strong correlation with the strengthening performance of chemically strengthened glass. + Impurity ions affect the dynamic balance of ion exchange; Li + As the sodium-lithium exchange proceeds, it will continue to enter the pure sodium molten salt, causing the sodium-lithium exchange degree to decrease. The ion exchange reaction formula is as follows:
[0042] Na + (Molten salt)+Li + (Glass) = Na + (Glass)+Li + (Molten Salt)
[0043] As the number of lithium ions in the molten salt increases, the reaction process will proceed from right to left, and the equilibrium will move to the left. According to the surface chemical equilibrium, Li + The increase in concentration will inevitably inhibit the exchange reaction of large-radius ions in the molten salt replacing small-radius ions in the microcrystalline glass, affecting the performance of the microcrystalline glass.
[0044] Compared with ordinary glass, the surface chemical equilibrium of microcrystalline glass-high temperature molten salt is more favorable for Li + Very sensitive to concentration changes, even at the ppm level + Changes in concentration will also cause a significant decrease in compressive stress intensity, thereby reducing the damage resistance of the microcrystalline glass. The size expansion of the microcrystalline glass will also decrease rapidly, resulting in a decrease in yield.
[0045] This molten salt contains Li + The problem that the increase in concentration will reduce the stress strength and product yield of microcrystalline glass is called lithium poisoning. + The adverse effects of poisoning on product performance and yield can be replaced by new molten salt, but this will increase costs and reduce efficiency. Alternatively, an ion sieve that can specifically purify lithium ions at the ppm level in the molten salt can be used, but the existing lithium ion sieve has low lithium absorption efficiency and poor thermal stability. It is easy to decompose at high temperatures, which affects the pH value of the molten salt and even corrodes the surface of the microcrystalline glass, causing the surface of the microcrystalline glass to become atomized.
[0046] The present application provides a lithium ion sieve, which is used for chemically strengthening microcrystalline glass. In terms of molar percentage, the lithium ion sieve includes the following components: 40%≤SiO2≤55%, 15%≤Al2O3≤30%, 20%≤Na2O<30%, and 0%≤MgO≤10%.
[0047] The lithium ion sieve provided in the present application has a reasonable structure and composition. When used in conjunction with molten salt, it can have both high thermal stability and high lithium absorption efficiency, is not prone to softening or decomposition, and is beneficial to maintaining the pH value of the molten salt. The lithium ion sieve can adsorb or extract impure metal ions in the molten salt, which is beneficial to the restoration of the activity of the molten salt, can support the chemical strengthening process of microcrystalline glass at higher temperatures, has low corrosiveness to microcrystalline glass, and greatly reduces pollution to the surface of the microcrystalline glass.
[0048] In the glass-based lithium ion sieve, SiO2 is a forming body and a skeleton constituting the glass topological structure. Its composition and content will affect the adsorption performance of the lithium ion sieve. In this application, in terms of molar percentage, 40%≤SiO2≤55%. The molar ratio content of SiO2 can be 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54% or 55%, etc., and of course, it can also be other values within the range of 40% to 55%, which is not limited here.
[0049] In glass-based lithium ion sieves, Al2O3 is also a component of the lithium ion sieve glass topological structure. In this application, in terms of molar percentage, 15%≤Al2O3≤30%. The molar ratio of Al2O3 can be 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29% or 30%, etc., and of course it can also be other values within the range of 15% to 30%, which is not limited here. Too high Al2O3 content may make the lithium ion sieve difficult to form. Controlling it within the above range can not only ensure the network topological structure of the lithium ion sieve, but also synergize with SiO2 to improve the exchange efficiency of the lithium ion sieve.
[0050] In some embodiments, in terms of molar percentage, 60%≤SiO2+Al2O3≤80%. Specifically, it can be 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79% or 80%, etc., and of course, it can also be other values within the range of 60% to 80%, which is not limited here. By controlling the total amount of SiO2+Al2O3, SiO2 and Al2O3 can form polar covalent bonds and ionic bonds, which is beneficial to maintain the structural stability of the lithium ion sieve under high temperature conditions and reduce the decomposition of the lithium ion sieve.
[0051] Na2O is an exosome and an important carrier for purifying lithium ions in molten salt through Na+-Li+ ion exchange reaction. However, too high a Na2O content can easily introduce too much non-bridging oxygen, resulting in a decrease in the glass transition temperature of the lithium ion sieve, a decrease in stability, and an increase in pH value.
[0052] In the present application, in terms of molar percentage, 20%≤Na2O<30%, and the molar ratio of Na2O can be 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 28.5%, 29% or 29.5%, etc., and of course, it can also be other values within the range of 20% to 30%, which is not limited here. Preferably, 20%≤Na2O≤29%.
[0053] In terms of molar percentage, the lithium ion sieve includes 0%≤MgO≤10%. MgO can improve the high temperature resistance of the lithium ion sieve, enhance the structural stability and reduce the pH value. Specifically, the molar ratio of MgO can be 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 8.5%, 9% or 10%, etc., and of course it can also be other values within the range of 0% to 10%, which is not limited here. Al2O3 and MgO can form Al2O3 in the SiO2 microtopological structure. 3+ / Mg2+ Four-coordinate, containing Al 3+ / Mg 2+ The tetraligand is an effective channel for lithium ion transport and can effectively improve the lithium absorption efficiency of the lithium ion sieve. Preferably, 0%≤MgO≤4.5%.
[0054] In some embodiments, in terms of molar percentage, 0.8≤Na2O / (MgO+Al2O3)≤1, and the above ratio can specifically be 0.8, 0.82, 0.85, 0.89, 0.91, 0.92, 0.95, 0.98, 0.99 or 1.0, etc., and of course, it can also be other values within the range of 0.8 to 1, which are not limited here. Controlling 0.8≤Na2O / (MgO+Al2O3)≤1 within this range can better achieve a balance between the high glass transition temperature and lithium absorption efficiency of the lithium ion sieve, so that the lithium ion sieve can have both high thermal stability and high lithium absorption efficiency when used in conjunction with molten salt, and is not prone to softening or decomposition.
[0055] In some embodiments, the glass transition temperature Tg of the lithium ion sieve satisfies: 600≤Tg≤800° C. That is, the lithium ion sieve can support the chemical strengthening process of microcrystalline glass at a higher temperature, has little corrosiveness to microcrystalline glass, and greatly reduces pollution to the surface of microcrystalline glass.
[0056] In a second aspect, the present application provides a lithium ion sieve, which is used for chemically strengthening microcrystalline glass. In terms of molar percentage, the lithium ion sieve comprises the following components: 35%≤SiO2≤45%, 10%≤Al2O3≤20%, 30%≤Na2O≤45%;
[0057] The lithium ion sieve also includes La2O3 and / or ZrO2, in molar percentage, 0%≤La2O3≤15%, 0%≤ZrO2≤10%.
[0058] The lithium ion sieve provided in the present application has a reasonable structure and composition. When used in conjunction with molten salt, it can have both high thermal stability and high lithium absorption efficiency, is not prone to softening or decomposition, and is beneficial to maintaining the pH value of the molten salt. The lithium ion sieve can adsorb or extract impure metal ions in the molten salt, which is beneficial to the restoration of the activity of the molten salt, can support the chemical strengthening process of microcrystalline glass at higher temperatures, has low corrosiveness to the microcrystalline glass, and will not cause pollution to the surface of the microcrystalline glass.
[0059] In the glass-based lithium ion sieve, SiO2 is a forming body and a skeleton constituting the glass topological structure. Its composition and content will affect the adsorption performance of the lithium ion sieve. In this application, in terms of molar percentage, 35%≤SiO2≤45%. The molar ratio content of SiO2 can be 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44% or 45%, etc., and of course, it can also be other values within the range of 35% to 45%, which is not limited here.
[0060] In glass-based lithium ion sieves, Al2O3 is also a component of the lithium ion sieve glass topological structure. In this application, in terms of molar percentage, 10%≤Al2O3≤20%. The molar ratio content of Al2O3 can specifically be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%, etc., and of course it can also be other values within the range of 10% to 20%, which are not limited here. Too high Al2O3 content may make the lithium ion sieve difficult to form. Controlling it within the above range can not only ensure the network topological structure of the lithium ion sieve, but also synergize with SiO2 to improve the exchange efficiency of the lithium ion sieve.
[0061] In some embodiments, in terms of molar percentage, 40%≤SiO2+Al2O3≤60%. Specifically, it can be 40%, 42%, 44%, 45%, 46%, 48%, 50%, 52%, 54%, 56%, 58% or 60%, etc., and of course, it can also be other values within the range of 40% to 60%, which are not limited here. By controlling the total amount of SiO2+Al2O3, SiO2 and Al2O3 can form polar covalent bonds and ionic bonds, which is beneficial to maintain the structural stability of the lithium ion sieve under high temperature conditions and reduce the decomposition of the lithium ion sieve.
[0062] Na2O is an exosome and an important carrier for purifying lithium ions in molten salt through Na+-Li+ ion exchange reaction. However, too high a Na2O content can easily introduce too much non-bridging oxygen, causing the glass transition temperature of the lithium ion sieve to drop.
[0063] In the present application, in terms of molar percentage, 30%≤Na2O≤45%, and the molar ratio of Na2O can be 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44% or 45%, etc., and of course, it can also be other values within the range of 30% to 45%, which is not limited here. Preferably, 30%≤Na2O≤38%.
[0064] In some embodiments, the molar content of La2O3 can be 0%, 0.5%, 1%, 3%, 5%, 7%, 9%, 10%, 12%, 13%, 14% or 15%, etc., and of course it can also be other values within the range of 0% to 15%, which is not limited here. The molar content of ZrO2 can be 0%, 0.5%, 1%, 3%, 5%, 7%, 9% or 10%, etc., and of course it can also be other values within the range of 0% to 15%, which is not limited here.
[0065] In some embodiments, in terms of molar percentage, 0%<La2O3+ZrO2≤25%. Specifically, it can be 0.1%, 0.5%, 1%, 3%, 5%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 23%, 24% or 25%, etc. Of course, it can also be other values within the range of 0% to 25%, which are not limited here. It can be understood that ZrO2 and La2O3 can effectively reduce the proportion of non-bridging oxygen in the microstructure of the glass and improve the thermal stability of the lithium ion sieve. Preferably, 5%≤La2O3+ZrO2≤25%.
[0066] In some embodiments, in terms of molar percentage, 1≤Na2O / (La2O3+ZrO2)≤15. The above ratio can specifically be 1, 1.5, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15, etc., and of course it can also be other values within the range of 1 to 15, which are not limited here. By controlling 1≤Na2O / (La2O3+ZrO2)≤15 within this range, the balance between the high glass transition temperature and the lithium absorption efficiency of the lithium ion sieve can be better achieved, so that the lithium ion sieve can have both high thermal stability and high lithium absorption efficiency when used in conjunction with molten salt, and is not prone to softening or decomposition.
[0067] In some embodiments, the glass transition temperature Tg of the lithium ion sieve satisfies: 500≤Tg≤700° C. That is, the lithium ion sieve can support the chemical strengthening process of microcrystalline glass at a higher temperature, has little corrosiveness to microcrystalline glass, and greatly reduces pollution to the surface of microcrystalline glass.
[0068] In this application, the lithium ion screen is obtained by screening through a machine learning model of big data. Specifically, the following steps are included:
[0069] Collecting glass sample data, and establishing a sample data set according to the glass sample data, wherein the glass sample data at least includes a glass component formula and a glass transition temperature parameter;
[0070] Train the sample data set and build an artificial neural network model;
[0071] The artificial neural network model is used to determine the relationship between the glass component formula and the glass transition temperature parameter, and multiple glass component parameters are screened according to the target glass transition temperature.
[0072] In the process of establishing the artificial neural network model, the artificial neural network model fits a large amount of glass sample data and constructs a mapping relationship between the glass composition formula and the glass transition temperature, such as Figure 1 as well as Figure 2 As shown, this mapping relationship can predict the glass transition temperature corresponding to the glass composition formula.
[0073] In this application, we conducted a large number of experimental verifications based on the series of glass component formula combinations output by the artificial neural network model. The specific steps include:
[0074] Weigh the corresponding raw materials according to the glass composition formula, mix the raw materials thoroughly, melt them at a high temperature of 1100°C to 1650°C and keep them warm for 2h to 8h to obtain glass liquid;
[0075] The glass liquid is solidified and formed to obtain a solid lithium ion sieve.
[0076] Specifically, the lithium ion sieve particles can be 5mm to 3cm granular, irregularly shaped and 0.3mm to 1mm thick sheet or a porous ion sieve with a pore size of 1mm to 10mm. The lithium ion sieve in the present application is not easy to decompose, and there is no boron, phosphorus, etc. precipitation to pollute or corrode the surface of the glass-ceramic glass.
[0077] The solidification molding process may specifically be at least one of an iron mold casting molding process, a water quenching molding process, a calendering molding process or a laser suspension melting molding process.
[0078] In some embodiments, the iron mold casting process is to pour the molten glass into iron molds of different sizes. During the cooling process, the glass naturally cracks and breaks into small pieces due to thermal stress, thereby obtaining a lithium ion sieve with a particle size of about 5 mm to 3 cm.
[0079] The water quenching forming process is to quench the glass liquid to obtain a granular lithium ion sieve, wherein the water quenching temperature is 10°C to 90°C, and the water quenching temperature can be 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C or 90°C, etc., and of course it can also be other values within the above range, which is not limited here. The particle size of the lithium ion sieve can be adjusted by adjusting the water quenching temperature, so that the particle size of the lithium ion sieve meets 5mm to 3cm, which can be 5mm, 7mm, 8mm, 1cm, 1.5cm, 2cm, 2.5cm, 2.8cm or 3cm, etc., and of course it can also be other values within the above range, which is not limited here.
[0080] The calendering process is to pour the glass liquid into the calendering machine, and to obtain the sheet ion sieve by external force calendering. The calendering process can also adjust the process to obtain the sheet ion sieve with a thickness in the range of 0.3mm to 2mm. The particle size of the sheet ion sieve can be 0.3mm, 0.4mm, 0.5mm, 0.6mm, 0.7mm, 0.8mm, 0.9mm, 1mm, 2mm, etc., and of course it can be other values within the above range, which is not limited here.
[0081] In other embodiments, the lithium ion sieve can also be melted by laser suspension, specifically using laser heating to melt the material, and then cooling to obtain lithium ion sieve particles. The particle size of the lithium ion sieve can be adjusted by adjusting the laser power and the suspension gas pressure, so that the particle size of the lithium ion sieve meets 1mm to 1cm, specifically 1mm, 3mm, 5mm, 7mm, 1cm, etc., of course, it can also be other values within the above range, which is not limited here.
[0082] The lithium ion sieve provided in the present application can be widely used in ultra-high temperature molten salt of glass and microcrystalline glass. The lithium ion sieve can adsorb or extract impurity metal ions in the molten salt, improve the lithium ion adsorption efficiency, and is beneficial to the restoration of the activity of the molten salt. It can support the chemical strengthening process of microcrystalline glass at higher temperatures, has little corrosiveness to microcrystalline glass, and will not cause pollution to the surface of the microcrystalline glass.
[0083] The present application also provides a chemically strengthened microcrystalline glass, wherein the chemically strengthened microcrystalline glass is prepared by the following method:
[0084] The glass-ceramics is placed in a molten salt containing a lithium ion sieve to carry out chemical ion exchange, thereby obtaining chemically strengthened glass-ceramics.
[0085] In some embodiments, the content of lithium ions in the molten salt is ≤1200ppm, specifically 1200ppm, 1100ppm, 1000ppm, 900ppm, 800ppm, 700ppm, 600ppm, 500ppm, 400ppm, 300ppm, etc., which is not limited here.
[0086] In the present application, the amount of lithium ion sieve added is less than the mass of the microcrystalline glass, thereby avoiding that too much space in the molten salt is occupied by the lithium ion sieve. The microcrystalline glass has a small space available and a low volume utilization rate.
[0087] In some embodiments, the molten salt includes at least one of sodium nitrate, sodium chloride, potassium nitrate, and potassium chloride.
[0088] The present application also provides a glass structural member, which includes the above-mentioned chemically strengthened microcrystalline glass. The glass structural member includes a laminate of glass and non-glass materials, a laminate of amorphous and crystalline materials, and glass-ceramics (including an amorphous phase and a crystalline phase). The glass structural member described in the present application includes strengthened glass or glass ceramic materials. The glass substrate is chemically strengthened by ion exchange, and the glass substrate includes various types of glass products, such as aluminosilicate glass, soda-lime glass, alkali metal aluminosilicate glass, etc., which are not limited here.
[0089] The present application also provides a display screen, which includes a cover plate, and the cover plate is made of the above-mentioned chemically strengthened microcrystalline glass.
[0090] The present application also provides an electronic device, the electronic device comprising the above-mentioned glass structure or the above-mentioned display screen. Specifically, the electronic device can be a mobile phone, a tablet computer, an e-reader, a laptop computer, a digital camera, a vehicle-mounted device, a television or a wearable device, a virtual reality (VR) terminal device, an augmented reality (AR) terminal device, or the like.
[0091] The following is a further description of the embodiments of the present invention in multiple embodiments. The embodiments of the present invention are not limited to the following specific embodiments. The embodiments can be appropriately modified within the scope of the unchanged main rights.
[0092]
Lithium ion screen
[0093] Step 01, weigh the corresponding raw materials according to the glass composition formula, mix the raw materials thoroughly, melt them at a high temperature of 1100°C to 1650°C and keep them warm for 6 hours to obtain glass liquid;
[0094] Step 02, pour the glass liquid into a 25cm*25cm iron mold. During the cooling process, the glass liquid naturally cracks and breaks into small pieces due to thermal stress, and a lithium ion sieve with a particle size of about 5mm to 3cm is obtained.
[0095] According to the above steps, Examples 1 to 15 were prepared. The glass component formulas of Examples 1 to 15, the Tg values predicted by the artificial neural network model, and the actually measured Tg values are shown in Table 1.
[0096] Table 1. Tg prediction values of lithium ion sieves with different composition formulas
[0097]
[0098] According to the test data of Examples 1 to 24, the artificial neural network model for predicting the glass transition temperature of glass provided in the present application can be beneficial to the screening of glass. The actual glass transition temperatures of lithium ion sieves of different components measured by differential scanning calorimetry are close to the predicted temperatures of the model, indicating that the artificial neural network model can more accurately predict the glass transition temperature of lithium ion sieves. 2 Close to 90%. Therefore, the artificial neural network model can also be used in the development of glass with other components to support the increasing customization demand for material performance in mobile electronic products.
[0099] According to Table 1 above, the lithium ion sieves provided in Examples 1 to 8 include the following components in terms of molar percentage: 40%≤SiO2≤55%, 15%≤Al2O3≤30%, 20%≤Na2O<30%, 0%≤MgO≤10%. According to the data of the actual glass transition temperature of the lithium ion sieve measured, the glass transition temperature of the lithium ion sieve satisfies 600°C≤Tg≤800°C.
[0100] The glass transition temperature of Examples 2 and 4 to 8 exceeds 650°C, which shows that the thermal stability of the lithium ion sieve is significantly improved, that is, by controlling 0.8≤Na2O / (MgO+Al2O3)≤1 within the above range, it is beneficial to further improve the stability of the network topology structure of the lithium ion sieve, and it is beneficial to further improve the thermal stability of the lithium ion sieve.
[0101] According to Table 1 above, the lithium ion sieve provided in Examples 9 to 13 includes the following components in terms of molar percentage: 35%≤SiO2≤45%, 10%≤Al2O3≤20%, 30%≤Na2O≤45%, 0%≤ZrO2≤10%. According to the data of the actual glass transition temperature of the lithium ion sieve measured, the glass transition temperature of the lithium ion sieve satisfies 500≤Tg≤700°C.
[0102] The glass transition temperature of Examples 10 to 13 exceeds 580°C, which shows that the thermal stability of the lithium ion sieve is significantly improved, that is, by controlling 1≤Na2O / (La2O3+ZrO2)≤15 within the above range, it is beneficial to further improve the stability of the network topology structure of the lithium ion sieve, which is beneficial to further improve the thermal stability of the lithium ion sieve.
[0103] According to Table 1 above, the lithium ion sieves provided in Examples 14 to 19 include the following components in terms of molar percentage: 35%≤SiO2≤45%, 10%≤Al2O3≤20%, 30%≤Na2O≤45%, and 0%≤La2O3≤15%. According to the data of the actual glass transition temperature of the lithium ion sieve measured, the glass transition temperature of the lithium ion sieve satisfies 500≤Tg≤700°C.
[0104] The glass transition temperature of Examples 15 to 19 exceeds 500°C, which shows that the thermal stability of the lithium ion sieve is significantly improved, that is, by controlling 1≤Na2O / (La2O3+ZrO2)≤15 within the above range, it is beneficial to further improve the stability of the network topology structure of the lithium ion sieve, which is beneficial to further improve the thermal stability of the lithium ion sieve.
[0105] According to Table 1 above, the lithium ion sieve provided in Examples 20 to 24 includes the following components in terms of molar percentage: 35%≤SiO2≤45%, 10%≤Al2O3≤20%, 30%≤Na2O≤45%, 0%≤La2O3≤15%, 0%≤ZrO2≤10%, and 0%<La2O3+ZrO2≤25%. According to the data of the actual glass transition temperature of the lithium ion sieve measured, the glass transition temperature of the lithium ion sieve satisfies 500≤Tg≤700°C.
[0106] The lithium ion sieve provided in Comparative Example 1 does not contain MgO, La2O3 and ZrO2, and Na2O / (MgO+Al2O3)>1. Their glass transition temperature is 520°C. The glass transition temperature is low, and the high-temperature stability of the lithium ion sieve is poor. When the strengthening temperature is ≥490°C, it will begin to soften and decompose, attaching to the surface of the microcrystalline glass to produce dirt. At the same time, a hydrolysis reaction occurs, corroding the surface of the microcrystalline glass, significantly increasing the pH of the furnace water, and reducing the life of the furnace water.
[0107] The lithium ion sieve provided in Comparative Example 2 does not have MgO, La2O3 and ZrO2 added, Na2O / (MgO+Al2O3)<0.8, and the lithium absorption efficiency of the lithium ion sieve is significantly reduced.
[0108]
Ion sieve lithium absorption efficiency test
[0109] The temperature of a molten salt containing 70% sodium nitrate and 30% potassium nitrate by mass is raised to 490°C, allowed to stand for 1 hour, and then a certain mass of lithium nitrate is added to the molten salt, while the pH value of the molten salt is adjusted to about 8.
[0110] 200 g of the lithium ion sieve in Table 1 were placed in sample racks and placed in the molten salt (50 kg) of the above-mentioned strengthening furnace, and taken out after 8 hours of ion replacement reaction.
[0111] According to the progress of the reaction, we sampled the high-temperature molten salt at different time periods and tested the Li + The concentration is related to the pH of the molten salt and is compared with the initial lithium ion concentration and the initial pH of the molten salt.
[0112] It should be noted that the Li + The change in concentration represents the lithium absorbing capacity of the lithium ion screen, and the change in pH value represents the effect of molten salt on the pH value of boiler water.
[0113] Among them, Li + The concentration was tested using an atomic spectrophotometer, and the pH value was tested using a pH tester; the test results are shown in Table 2.
[0114] Table 2. Effect of lithium ion sieves of embodiments and comparative examples on molten salt
[0115]
[0116]
[0117] According to the data in Table 2, the lithium ion sieve improved in the present application has little effect on the pH of the molten salt. During the chemical strengthening treatment of the microcrystalline glass, the corrosion of the microcrystalline glass surface caused by changes in the acidic and alkaline environment can be effectively reduced, and the whitening and fogging phenomenon of the glass can be reduced.
[0118] Figure 3 This is a comparison chart of the lithium absorption efficiency of the lithium ion sieve provided in Example 6 of the present application and the lithium ion sieves provided in Comparative Examples 1 and 2. Figure 4 This is a comparison chart of the effects of the lithium ion sieve provided in Example 6 of the present application and the lithium ion sieve provided in Comparative Examples 1 and 2 on the pH value of the molten salt; Figure 3 as well as Figure 4 As shown, the lithium absorption efficiency of the lithium ion sieve provided in Example 6 increased by 400% after adding the reaction for 0.5h, and increased by 50% after adding the reaction for 8h. In addition, during the entire ion exchange reaction, the lithium ion sieve has high thermal stability and has little effect on the pH value of the molten salt. It can be seen that the lithium ion sieve provided in this application can support the chemical strengthening of microcrystalline glass at a higher temperature, broadening the processing window of the chemical strengthening process of microcrystalline glass.
[0119] According to the test data of Example 12, Example 17 and Example 20, the addition of La2O3 and / or ZrO2 improves the lithium absorption efficiency of the lithium ion sieve compared with that of Comparative Example 2, and during the entire ion exchange reaction, compared with Comparative Example 1, the lithium ion sieve has a very high thermal stability and has little effect on the pH value of the molten salt.
[0120]
Chemical strengthening treatment of glass-ceramics
[0121] The present invention further illustrates the use method and effect of the ion sieve in strengthening microcrystalline glass. First, prepare the furnace water composition, temperature and pH as shown in Table 3. The ion sieve and the microcrystalline glass are put into the tempering furnace at the same time, and the total mass of the input is 30%-50% of the total weight of the microcrystalline glass. After being kept at a specific strengthening temperature for a specific time, the furnace water sample is taken to test the Li+ concentration and pH. After the microcrystalline glass is cleaned, dried and polished, the stress is tested using an SLP2000 stress meter, and the center extrusion strength is tested using a universal testing machine. As shown in Table 3, the lithium ion sieve used in the actual measurement example can better maintain the Li+ concentration and pH of the molten salt with less ion sieve input. The obtained microcrystalline glass also has higher stress strength and better surface quality, and therefore has higher anti-extrusion strength.
[0122] It is worth noting that the ion screen can be put into the strengthening furnace before, after or during strengthening. It can be put into the strengthening furnace at the same time as the microcrystalline glass or at different times.
[0123] Table 3. Effects of lithium ion sieves of examples and comparative examples on the properties of chemically strengthened microcrystalline glass
[0124]
[0125]
[0126] According to the test data of Comparative Example 1 and Example 12, in the lithium ion sieve (SiO2+Al2O3+Na2O+ZrO2) system, when 30%≤Na2O≤38%, 5%≤La2O3+ZrO2≤25%, an appropriate amount of ZrO2 and / or La2O3 is introduced to effectively reduce the proportion of non-bridging oxygen in the microstructure of the lithium ion sieve, improve the thermal stability of the lithium ion sieve, thereby supporting the chemical strengthening of microcrystalline glass at a higher temperature, and broadening the processing window of the microcrystalline glass chemical strengthening process.
[0127] According to the test data of Comparative Example 1 and Example 6, in the lithium ion sieve (SiO2+Al2O3+Na2O+MgO) system, when 20%≤Na2O≤29%, the proportion of non-bridging oxygen in the microstructure of the lithium ion sieve can be effectively reduced, and the thermal stability of the lithium ion sieve can be improved, thereby supporting the chemical strengthening of the microcrystalline glass at a higher temperature and broadening the processing window of the microcrystalline glass chemical strengthening process.
[0128] Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the claims. Any technical personnel in this field may make several possible changes and modifications without departing from the concept of the present application. Therefore, the scope of protection of the present application shall be based on the scope defined by the claims of the present application.
Claims
1. A lithium ion sieve, which is used for chemically strengthening microcrystalline glass, characterized in that: In terms of molar percentage, the lithium ion sieve comprises the following components: 40%≤SiO2≤55%, 15%≤Al2O3≤30%, 20%≤Na2O<30%, 0%≤MgO≤10%.
2. The lithium ion sieve according to claim 1, characterized in that: In terms of mole percentage, 20% ≤ Na2O ≤ 29%, 0% ≤ MgO ≤ 4.5%.
3. The lithium ion sieve according to claim 1, characterized in that: In terms of mole percentage, 60%≤SiO2+Al2O3≤80%.
4. The lithium ion sieve according to any one of claims 1 to 3, characterized in that: In terms of mole percentage, 0.8≤Na2O / (MgO+Al2O3)≤1.
5. The lithium ion sieve according to any one of claims 1 to 3, characterized in that: The glass transition temperature Tg of the lithium ion sieve satisfies: 600°C≤Tg≤800°C.
6. A lithium ion sieve, which is used for chemically strengthening microcrystalline glass, characterized in that: In terms of molar percentage, the lithium ion sieve comprises the following components: 35%≤SiO2≤45%, 10%≤Al2O3≤20%, 30%≤Na2O≤45%; The lithium ion sieve also includes La2O3 and / or ZrO2, in molar percentage, 0%<La2O3+ZrO2≤25%.
7. The lithium ion sieve according to claim 6, characterized in that: In terms of mole percentage, 30%≤Na2O≤38%, 5%≤La2O3+ZrO2≤25%.
8. The lithium ion sieve according to claim 6, characterized in that: In terms of mole percentage, 40%≤SiO2+Al2O3≤60%.
9. The lithium ion sieve according to any one of claims 6 to 8, characterized in that: In terms of mole percentage, 1≤Na2O / (La2O3+ZrO2)≤15.
10. The lithium ion sieve according to any one of claims 6 to 8, characterized in that: The glass transition temperature Tg of the lithium ion sieve satisfies: 500≤Tg≤700°C.
11. A chemically strengthened glass-ceramic, characterized in that: The chemically strengthened glass-ceramics is prepared by the following method: The glass-ceramics is placed in a molten salt containing the lithium ion sieve according to any one of claims 1 to 10 for chemical ion exchange to obtain chemically strengthened glass-ceramics.
12. The chemically strengthened glass-ceramics according to claim 11, characterized in that: The molten salt includes at least one of sodium nitrate, sodium chloride, potassium nitrate and potassium chloride.
13. A glass structural member, characterized in that: The glass structural member includes the chemically strengthened glass-ceramics according to any one of claims 11 to 12.
14. A display screen, characterized in that: The display screen comprises a cover plate, and the cover plate is made of the chemically strengthened microcrystalline glass according to any one of claims 11 to 12.
15. An electronic device, characterized in that: The electronic device comprises the glass structure according to claim 13 or the display screen according to claim 14.
Citation Information
Cited By
Ion sieve and application thereof, and regeneration method of failed ion sieve
CN121651376A